2021
DOI: 10.1016/j.medj.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Host Interactome and Proteomic Survey Reveal Potential Virulence Factors Influencing SARS-CoV-2 Pathogenesis

Abstract: Summary Background The ongoing coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a global public health concern due to relatively easy person-to-person transmission and the current lack of effective antiviral therapy. However, the exact molecular mechanisms of SARS-CoV-2 pathogenesis remain largely unknown. Methods Genome-wide screening was used to establish intraviral and viral-host inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
447
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(500 citation statements)
references
References 69 publications
30
447
3
2
Order By: Relevance
“…In addition, Huntington, Parkinson’s and Alzheimer’s disease related pathways were significantly enriched among the identified interaction partners (P-value cut-off 0.05 (FDR)) (Extended Figure 2B). We next compared our protein interaction data with two previously published AP-MS studies that were also performed in HEK293 cells 13,14 . We observed that there is little interaction partner overlap among the different reports, highlighting the variability of the experimental and/or statistical analyses employed in the various studies to catalogue the virus-host PPIs (see discussion) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Huntington, Parkinson’s and Alzheimer’s disease related pathways were significantly enriched among the identified interaction partners (P-value cut-off 0.05 (FDR)) (Extended Figure 2B). We next compared our protein interaction data with two previously published AP-MS studies that were also performed in HEK293 cells 13,14 . We observed that there is little interaction partner overlap among the different reports, highlighting the variability of the experimental and/or statistical analyses employed in the various studies to catalogue the virus-host PPIs (see discussion) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we report the biological impact of the SARS-CoV-2 N protein on host cells. Starting from a proteomic workflow, we found that there is little overlap across studies that recently reported virus-host PPIs for SARS-CoV-2 proteins 13,14 . This observation is perhaps not surprising due to varied experimental and statistical analyses employed across different studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another group expressed SARS-CoV-2 proteins in cell lines to elucidate the interactome of the viral proteins with host proteins. 75 The viral proteins were found to interact with almost 256 host cellar proteins affecting multiple pathways related to essential cellar functioning such as ATP biosynthesis mRNA transport, nucleotide-excision repair, translation initiation, and metabolic processes such as cellular amino acid and reactive oxygen species metabolism. Of particular importance was a finding that implicated the interaction between viral nonstructural protein 10 and NF-κB-repressing factor (NKRF), which in turn induces expression of chemokines such as interleukin-8 (IL-8).…”
Section: Application Of “Omics” Technologies In Disease Diagnosis Andmentioning
confidence: 99%
“…Chemokines like IL-8 trigger neutrophil chemotaxis, where these neutrophils reach on-site and release more pro-inflammatory compounds, and as a result, additional inflammatory signals are activated. 75 , 76 …”
Section: Application Of “Omics” Technologies In Disease Diagnosis Andmentioning
confidence: 99%